Raw Jojoba Oil as a Sustainable Fuel to Diesel Engines and Comparison with Diesel Fuel - Mohamed Y. E. Selim; Mamdouh T. Ghannam; Bishoy N. Abdo; Youssef A. Attai; Mohsen S. Radwan (Energies, 2022)
Raw Jojoba oil was used in a direct-injection diesel engine without any engine modifications and compared with both diesel fuel and 50/50 raw Jojoba/diesel. The measured parameters included the rheological properties measured in the range of shear rate from 100 to 500 1/s. Distillation data were presented for raw Jojoba oil compared to diesel. The parameters included exhaust gas analysis, block vibration, sound noise, and the combustion pressure and its rise rate. Averaged pressure-crank angle, vibration, and its frequency spectrum and sound level were presented. Data also included brake power, specific fuel consumption, and exhaust temperatures for all fuels used. For Jojoba oil, the engine did not exhibit low power output or specific fuel consumption. Exhaust temperatures, smoke opacity, and NOx emissions were lower than diesel case. Noise for Jojoba was higher than diesel case. The engine block vibration was concentrated towards the low frequency range.